2016
DOI: 10.1002/adma.201601710
|View full text |Cite
|
Sign up to set email alerts
|

DNA‐Nanostructure–Gold‐Nanorod Hybrids for Enhanced In Vivo Optoacoustic Imaging and Photothermal Therapy

Abstract: A functional cancer theranostic nanoplatform is developed, specifically tailored toward the optoacoustic modality by combining gold nanorods with DNA nanostructures (D-AuNR). DNA origami is used as an efficient delivery vehicle owing to its prominent tumor-targeting property. The D-AuNR hybrids display an enhanced tumor diagnostic sensitivity by improved optoacoustic imaging and excellent photothermal therapeutic properties in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
163
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 198 publications
(171 citation statements)
references
References 62 publications
(45 reference statements)
4
163
0
4
Order By: Relevance
“…ChemBioChem 2020, 21,[33][34][35][36][37][38][39][40][41][42][43][44] www.chembiochem.org increased by around 15 %( from 68.3, 71.8 and 70.5 %t o8 5.8, 86.2 and 86.3 %f or cross, rectangle and triangle shapes,r espectively) if the reactionw as performed at an elevated temperatureo f3 78C, relative to the results obtained at commonly used room temperature.…”
Section: Introductionmentioning
confidence: 87%
See 2 more Smart Citations
“…ChemBioChem 2020, 21,[33][34][35][36][37][38][39][40][41][42][43][44] www.chembiochem.org increased by around 15 %( from 68.3, 71.8 and 70.5 %t o8 5.8, 86.2 and 86.3 %f or cross, rectangle and triangle shapes,r espectively) if the reactionw as performed at an elevated temperatureo f3 78C, relative to the results obtained at commonly used room temperature.…”
Section: Introductionmentioning
confidence: 87%
“…Building on this, Du and co‐workers used such a system to combine photothermal therapy with optoacoustic imaging to also enable diagnostic imaging functionality . In their excellent review on the topic, Li and Chen explain that optoacoustic imaging (also called photoacoustic imaging) is an imaging technique in which a laser light is directed onto the tissue to be imaged and endo‐ or exogenous chromophores adsorb this light and then release it as heat, causing a rapid thermoelastic expansion, which generates a wide‐band ultrasound wave that can then be detected and processed to give an image .…”
Section: Special Applications In Interfacing With the Cellmentioning
confidence: 99%
See 1 more Smart Citation
“…Thereafter, Ding's group demonstrated that the DO‐AuNR complex showed a significant photoacoustic imaging effect (Figure c). The accumulation of DO‐AuNR in tumor was confirmed by dark‐field images and inductively coupled plasma‐mass spectrometry (ICP‐MS), which indicated the promising application of DO‐AuNR in tumor diagnosis …”
Section: Application Of Dna Nanostructuresmentioning
confidence: 92%
“…After observing the efficient photothermal therapy effect based on the DNA origami-GNR complex, Tian and co-workers subsequently developed GNR-loaded triangular DNA origami to function as an optoacoustic imaging agent. [35] GNR-loaded DNA origami can act as an efficient contrasta gent to achieve enhanced imaging quality with ad ecreased dose. Photothermal treatment based on this DNA origami-GNR complexd emonstrated efficient inhibition of tumor growth in vivo (Figure 3b).…”
Section: Delivery Of Gnrsmentioning
confidence: 99%